Functionally-selective inhibition of threshold sodium currents and excitability in dorsal root ganglion neurons by cannabinol - Mohammad-Reza Ghovanloo; Philip R. Effraim; Sidharth Tyagi; Peng Zhao; Sulayman D. Dib-Hajj; Stephen G. Waxman (Communications Biology)
Abstract Cannabinol (CBN), an incompletely understood metabolite for ∆9-tetrahydrocannabinol, has been suggested as an analgesic. CBN interacts with endocannabinoid (CB) receptors, but is also reported to interact with non-CB targets, including various ion channels. We assessed CBN effects on voltage-dependent sodium (Nav) channels expressed heterologously and in native dorsal root ganglion (DRG) neurons. Our results indicate that CBN is a functionally-selective, but structurally-non-selective Nav current inhibitor. CBN’s main effect is on slow inactivation. CBN slows recovery from slow-inactivated states, and hyperpolarizes steady-state inactivation, as channels enter deeper and slower inactivated states. Multielectrode array recordings indicate that CBN attenuates DRG neuron excitability. Voltage- and current-clamp analysis of freshly isolated DRG neurons via our automated patch-clamp platform confirmed these findings. The inhibitory effects of CBN on Nav currents and on DRG neuron excitability add a new dimension to its actions and suggest that this cannabinoid may be useful for neuropathic pain.